CORRELATION BETWEEN DISCHARGE PLANNING IMPLEMENTATION AND PATIENT RE-ADMISSION USING THE LACE INDEX IN THE ADULT INPATIENT ROOM AT THE HOSPITAL - Elasari, Yunina; Wulandari, Rizki Yeni; Nugroho, Tri Adi (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2026)
Background: Hospital readmission is a key indicator of the quality and continuity of patient care. In Indonesia, readmission rates have been reported at approximately 8.8%, contributing to increased healthcare costs ranging from 104% to 113% of initial treatment expenses. Effective discharge planning is essential to ensure continuity of care and reduce the likelihood of avoidable readmissions.Objective: This study aimed to examine the relationship between the implementation of discharge planning and hospital readmission risk, as measured using the LACE index.Methods: A correlational study with a cross-sectional design was conducted among 100 patients admitted to adult inpatient wards. Participants were selected using proportionate stratified random sampling. Inclusion criteria included patients who were conscious, had limb disorders, chronic illnesses, or long-term wound care needs, and required assistance with daily activities upon discharge. Data were collected using a validated discharge planning questionnaire and the LACE index to assess readmission risk. Statistical analysis was performed using the Gamma test to determine the association between variables, with significance set at p < 0.05.Results: The findings showed that 57% of respondents had a moderate risk of readmission based on the LACE index, while 48% experienced a high level of discharge planning implementation. A statistically significant relationship was found between discharge planning implementation and readmission risk (p = 0.001), indicating that better discharge planning is associated with lower risk of hospital readmission.Conclusions: The study highlights the critical role of comprehensive discharge planning in reducing hospital readmissions. Early and continuous implementation of discharge planning from admission through discharge can enhance continuity of care and improve the efficiency of nursing services. These findings provide important implications for hospital management in strengthening discharge planning practices as part of quality improvement strategies.